Citation content/context data as a source for research cooperation analysis. (2nd July 2020) - Parinov, Sergey; Antonova, Victoria
Using citation relationships, one can build three groups of papers: (1) the papers of a selected author; (2) those papers cited by the author; (3) papers citing the author. Authors of papers from these three groups can be presented as a fragment of a research cooperation network, because they use/cite research outputs of each other. Their papers' full texts and especially the contexts of their in-text citations contain some information about the character of this research cooperation. We present a concept of research cooperation, based on publications and the current results of the Cirtec project for building the research cooperation characteristics. This work is based on the processing of citation content/context data. The results include an on-line service for authors to monitor the citation content data extractions and three types of built indicators/parameters: co-citation statistics, spatial distribution of citations over papers' body and topic models for citation contexts.